Genomics insights into different cellobiose hydrolysis activities in two Trichoderma hamatum strains - Cheng, Peng; Liu, Bo; Su, Yi; Hu, Yao; Hong, Yahui; Yi, Xinxin; Chen, Lei; Su, Shengying; Chu, Jeffrey S. C.; Chen, Nansheng; Xiong, Xingyao (Microbial cell factories, 2017)
Efficient biomass bioconversion is a promising solution to alternative energy resources and environmental issues associated with lignocellulosic wastes. The Trichoderma species of cellulolytic fungi have strong cellulose-degrading capability, and their cellulase systems have been extensively studied. Currently, a major limitation of Trichoderma strains is their low production of β-glucosidases. We isolated two Trichoderma hamatum strains YYH13 and YYH16 with drastically different cellulose degrading efficiencies. YYH13 has higher cellobiose-hydrolyzing efficiency. To understand mechanisms underlying such differences, we sequenced the genomes of YYH13 and YYH16, which are essentially identical (38.93 and 38.92 Mb, respectively) and are similar to that of the T. hamatum strain GD12. Using GeneMark-ES, we annotated 11,316 and 11,755 protein-coding genes in YYH13 and YYH16, respectively. Comparative analysis identified 13 functionally important genes in YYH13 under positive selection. Through examining orthologous relationships, we identified 172,655, and 320 genome-specific genes in YYH13, YYH16, and GD12, respectively. We found 15 protease families that show differences between YYH13 and YYH16. Enzymatic tests showed that exoglucanase, endoglucanase, and β-glucosidase activities were higher in YYH13 than YYH16. Additionally, YYH13 contains 10 families of carbohydrate-active enzymes, including GH1, GH3, GH18, GH35, and GH55 families of chitinases, glucosidases, galactosidases, and glucanases, which are subject to stronger positive selection pressure. Furthermore, we found that the β-glucosidase gene (YYH1311079) and pGEX-KG/YYH1311079 bacterial expression vector may provide valuable insight for designing β-glucosidase with higher cellobiose-hydrolyzing efficiencies. This study suggests that the YYH13 strain of T. hamatum has the potential to serve as a model organism for producing cellulase because of its strong ability to efficiently degrade cellulosic biomass. The genome sequences of YYH13 and YYH16 represents a valuable resource for studying efficient production of biofuels.